Hubungan Pemberian Asi Eksklusif Dengan Pertumbuhan Dan Perkembangan Pada Bayi Di wilayah Kerja BPM Rosna Am.Keb Pematang Siantar - Elnur Charismawati Zebua; Dessy Ratna Sari Sembiring; Labora Br Manurung; Marta Armita Br Silaban (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Breastfeeding is the first, most important and best food in the early life and natural life of a baby. Coverage of exclusive breastfeeding is still low. Exclusive breastfeeding is influenced by several factors, including the mother's knowledge and about exclusive breastfeeding.Objective: to find out the mother's relationship with the mother's knowledge and exclusive breastfeeding.Design: This type of study is an analytical study that uses a cross-sectional design. The main population of this study was mothers with children aged 7-12 months in the working area of ​​Muara Badak Health Center, a total of 120 people, a sample of 92 people. The sampling technique uses purposive sampling. Chi-square is used to analyze the data.Result: The characteristics of the respondents were mainly 21-30 years old, a total of 64 people (69.6%), 41 people with a high school diploma (44.6%) and a total of 47 people (51.1%) with professions such . like IRT. 64 subjects (69.6%) had poor maternal knowledge of exclusive breastfeeding, while 28 subjects (30.4%) had good knowledge of exclusive breastfeeding. 51 mothers did not exclusively breastfeed (55.4%) and 41 mothers (44.6%). In, the association of mother and knowledge with exclusive breastfeeding, p-value: 0.006 andlt;α: 0.05, so Ho is rejected and Ha is accepted.Conclusion: The relationship of mother and knowledge to exclusive breastfeeding.Proposal: Counseling is needed on the importance of exclusive breastfeeding and proper storage of breast milk workplace.